Water-soluble coordination polymers of CuII with tetrachloroterephthalate: resin-assisted solvothermal synthesis, structural transformation and luminescence properties. (9th July 2015) - Dai, Ai-Qi; Yan, Qi; Zhong, Jing; Chen, Sheng-Chun; He, Ming-Yang; Chen, Qun
A CuII coordination polymer with tetrachloroterephthalate (BDC–Cl4), {[Cu(BDC–Cl4)(DMF)2]·H2O}n has been synthesised by a resinassisted solvothermal method. The complex has a one-dimensional (1-D) [Cu2(BDC–Cl4)2]n double chain structure in the solid state, exhibits high aqueous solubility, and further evaporation of its aqueous solution yielded a further coordination polymer {[Cu(BDC–Cl4) (H2O)4]·4H2O}n, which displays a 1-D [Cu(BDC–Cl4)]n single chain structure. IR spectroscopy, molar electrical conductivity, thermal stability and luminescence properties of both complexes have also been investigated.